PERENCANAAN ULANG TATA LETAK FASILITAS PRODUKSI UNTUK PENANGANAN MASALAH MATERIAL HANDLING DAN TATA RUANG DI PT. JAMU INDONESIA SIMONA - Artika Wulansari; Antoni Yohanes (Jurnal Ilmiah Dinamika Teknik, 2010)
Arrange situation which better in company will improve activity efficiency and effectiveness, so that not generate current of return inter department as well as minimization is expense of transfer of material. Problems of arising out in PT. Jamu Indonesia of Simona is how to arrange to arrange facility situation produce effectively so that material stream and minimization of[is expense of material of handling during production process take place. After seeing layout early, there are some process transfer of too material far effect of arrangement of less efficient production facility. Hence to lessen the expense of material of handling which too big used method of From Chart to constructively Facility Location Layout running and comparison [among/between] result of change running 2 change and department 3 data-processing department. The value with FLL running three measurement of distance method, Rectilinear Distance, Squared Euclidean Distance and of Euclidean Distance got most minimum contribution value that is method of Euclidean Distance. Later; then pursuant to degree of contiguity between room use analysis of Activity Relationship Chart (ARC) made proposal of layout new. After FLL layout running analyze ARC, obtained minimum total cost change 2 department. To get best proposal layout, hence minimum total cost from third used to be measurement of distance method to be recounted to use method of Euclidean Distance as comparison. After enumeration got minimum total cost equal to 73.627,43, that is layout analyze ARC method of Rectilinear Distance and of Euclidean Distance, so that decided layout result of analysis of ARC this weared as proposal layout. Keywords:Layout, From to Chart, Activity Relationship Chart (ARC), Facility Location Layout (FLL)